2014
DOI: 10.1111/jvim.12325
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Cats with Hypertrophic Cardiomyopathy

Abstract: BackgroundCats with hypertrophic cardiomyopathy (HCM) are at risk for development of systemic thromboembolic disease. However, the relationship between platelet activation state and cardiovascular parameters associated with HCM is not well described.ObjectivesTo characterize platelet activation by flow cytometric evaluation of platelet P‐selectin and semiquantitative Western blot analysis of soluble platelet‐endothelial cell adhesion molecule‐1 (sPECAM‐1).AnimalsEight normal healthy cats (controls) owned by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 43 publications
2
43
1
Order By: Relevance
“…This finding further suggests the conclusion that cats with genetic predisposition to HCM have procoagulant platelets that predispose them to intracardiac thrombi formation and increased risk for ATE. Platelet P‐selectin expression in this population of cats was generally higher than previously reported . The differences in results were likely because of the use of different CD62P antibodies, in vitro activation from sample handing and centrifugation, age and genetic differences between the studied populations.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This finding further suggests the conclusion that cats with genetic predisposition to HCM have procoagulant platelets that predispose them to intracardiac thrombi formation and increased risk for ATE. Platelet P‐selectin expression in this population of cats was generally higher than previously reported . The differences in results were likely because of the use of different CD62P antibodies, in vitro activation from sample handing and centrifugation, age and genetic differences between the studied populations.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, the use of citrate as an anticoagulant might have inhibited PMV formation because low extracellular calcium concentration prevents activation of calcium‐dependent calpain, which facilitates PMV formation by degrading structural proteins such as actin‐binding protein . Because cats with severe HCM were demonstrated to have a significant increase in PMV, it is also possible that PMV formation could be associated with disease severity and that the lack of clinical HCM precluded any significant changes in PMV formation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systemic hypercoagulable state occurs in 50% of cardiomyopathic felines with spontaneous echocardiographic contrast (or “smoke”) with or without a left atrial (LA) thrombus, and in 56% of felines with ATE and LA enlargement . Thromboembolism in felines with CM is likely an effect resulting from platelet activation (due to altered blood flow and shear stress within the cardiovascular system) and coagulation factors (in areas of blood stasis within the left atrium) . This increased platelet activity in felines could provide a more rigorous model for the evaluation of the biocompatibility of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of hypercoagulability in cats presenting with CE exists, but the sensitivity of a single or several markers has been low. Studies using platelet aggregometry support an increased platelet activation level in cats with HCM, and one study demonstrated higher PMP concentrations among Maine Coon cats with severe HCM compared with those of healthy mixed‐breed cats . Further investigations into PMPs as a prothrombotic risk factor in HCM are warranted.…”
Section: Introductionmentioning
confidence: 99%